Hypertonic saline achieves superior brain relaxation in tumor craniotomy: An updated systematic-network meta-analysis - Khairunnisai Tarimah, MD; Lalu B. Bramawangsa, MD; Christian J. Suhardi, MD; Elvan Wiyarta, MD; Dewi Y. Bisri, MD (Journal of Taibah University Medical Sciences, 2024)
الملخص: أهداف البحث: يتطلب بضع القحف لورم الدماغ استرخاء الدماغ، ويتم ذلك عن طريق تقليل الضغط داخل الجمجمة. العلاج الأسموي بفرط الأسمولية هو تقنية يمكن استخدامها لتقليل الضغط داخل القزحية. تهدف هذه الدراسة إلى تحديث الدراسات السابقة لتقييم فعالية وسلامة استخدام المحلول الملحي مفرط التوتر مقارنة بالمانيتول في خفض الضغط داخل الجمجمة لدى مرضى الأورام الدماغية البالغين الخاضعين لجراحة فتح الجمجمة. طرق البحث: تم إجراء بحث منهجي في خمس قواعد بيانات من عام 2013 إلى ديسمبر 2023 لتحديد التجارب العشوائية المضبوطة التي تقارن المحلول الملحي مفرط التوتر بالمانيتول. تم إجراء التحليل التلوي التقليدي، والتحليل البايزي، وتحليل التسلسل التجريبي، وتقييم جودة التجارب. النتائج: شملت الدراسة 11 تجربة عشوائية مضبوطة بمجموع 593 مشاركا. ارتبط المحلول الملحي مفرط التوتر بتحسن كبير في استرخاء الدماغ، وانخفاض كبير في إنتاج البول، وانخفاض كبير في مدخلات السوائل. كما ارتبط بارتفاع كبير في متوسط ضغط الدم الشرياني ومستوى الصوديوم في البلازما. لم يكن هناك فرق كبير في ضغط الإرواء الدماغي بين المجموعتين. أظهر التحليل البايزي تفوق المحلول الملحي مفرط التوتر بتركيز 3% بجرعة 5 مل/كجم في تحقيق استرخاء الدماغ. الاستنتاجات: المحلول الملحي مفرط التوتر متفوق على المانيتول في تحقيق استرخاء الدماغ الأمثل، والحفاظ على تدفق الدم المستقر، وتقليل التأثيرات المدرة للبول. ومع ذلك، من المهم ملاحظة أن استخدامه قد يؤدي إلى زيادة مستويات الصوديوم في البلازما. الجرعة الموصى بها لتحقيق استرخاء الدماغ هي المحلول الملحي مفرط التوتر بتركيز 3% بجرعة 5 مل لكل كجم من وزن الجسم. Abstract: Background: Brain tumor craniotomy requires relaxation of the brain through decreasing the intracranial pressure (ICP). Osmo-hyperosmolar therapy can be used to lower the ICP. Objectives: This study was aimed at updating previous studies to determine the effects and safety of using hypertonic saline (HTS) and mannitol to decrease ICP in adult patients with brain tumors undergoing craniotomy. Methods: To identify randomized controlled trials (RCTs) comparing HTS vs mannitol, we performed a systematic literature search according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines, by examining records from 2013 to December of 2023 in five databases. The primary outcome was brain relaxation, and the secondary outcomes were cerebral perfusion pressure (CPP), urine output (UO), fluid input, mean arterial pressure (MAP), and plasma sodium. Conventional meta-analysis, Bayesian meta-insight analysis, trial-sequential analysis, and trial quality assessment were conducted. Results: Eleven RCTs involving 593 participants were included in the meta-analysis. Use of HTS, compared with mannitol, was associated with significantly greater brain relaxation, and significantly lower UO and fluid input. HTS was also significantly associated with elevated MAP. Plasma sodium was significantly higher in the HTS group than the mannitol group. No significant difference in CPP was observed between groups. Trial sequential analysis indicated true significance for the brain relaxation outcomes. Bayesian analysis demonstrated the superiority of 3% HTS at 5 ml/kg in achieving brain relaxation, followed by 3% HTS at 5.3 ml/kg and 20% mannitol at 5 ml/kg. Conclusions: HTS is superior to mannitol in achieving optimal brain relaxation, maintaining stable blood flow, and minimizing diuretic effects. However, use of HTS during tumor craniotomy procedures can increase plasma sodium levels. The optimal dose for achieving brain relaxation appears to be 3% HTS at 5 ml/kg body weight.